I. O. Zelena: LEXICAL AND SEMANTIC FEATURES OF MODERN ENGLISH TEXTS OF PUBLICISTIC STYLE - Zelena, I. O. (Linguistic Bulletin (Movoznavchyi Visnyk), 2021)
The article deals with lexical and semantic features of modern English journalism. The purpose of the paper is to reveal lexical and semantic features of modern English texts of publicistic style (based on National Geographic). There has been given a brief overview of publicistic style, outlined its functions, namely informational, influencing, expressive and emotive. It has been concluded that publicistic style absorbs features of other functional styles mainly due to the fact of intertwining and interaction of language styles. Such style-forming features of publicistic style as evaluativeness, passion, emotionality, conciseness of expression, communicative and pragmatic focus on their recipients have been emphasized. To enhance the expressiveness and emotionality of the author’s intentions, various lexical and semantic features of the organization of a publicistic text have been considered, namely epithets, metaphors, stylistic comparisons, insert constructions and clichés, inversions etc. The article also gives brief summarized data on the frequency of usage of the stylistic tropes and the figures showing the most productive and the least productive forms.